The Sidney Siegel tradition: The divergence of behavioral and experimental economics at the end of the 1980s - Andrej Svorenécík (Duke University, Center for the History of Political Economy (CHOPE), 2016)
Over two days in February 1988, several key experimental economists and cognitive psychologists met to explore the possibilities of joint research promoted by the Sloan and Russell Sage Foundations under the rubric behavioral economics. The original vision that the meeting could open a line of inquiry on the growing body of behavioral "anomalies" and their robustness in a market setting proved naive. The divide between both camps was too big to bridge given the fundamentally different approaches to experimentation. The article traces how the work of Sidney Siegel, a psychologist briefly active in the 1950s, was recast by experimental economists as the basis of their experimental research, including the emphasis on performance-based payments of experimental subjects and avoiding deception. My reconstruction of this meeting and its aftermath sheds new light on the origin of the divergence of experimental and behavioral economics at the end of the 1980s.
Keywords: B21; B31; C90; C91; D03; 330; experimental economics; behavioral economics; Sidney Siegel; Behavioral Economics Program